Funciones desempeñadas como asistente contable en la empresa Transportes y Servicios del Norte SAC - Castro Reyes, Mayra Elizabeth (2019)
This report of the work of professional sufficiency, has been developed in the company Transportes y Servicios del Norte SAC., In the District of Moche, Province of Trujillo, La Libertad Region, and has as a general objective, to identify the types of payments, the suppliers and payment terms in the company Transportes y Servicios del Norte SAC. After presenting the main functions performed as an accounting assistant, the main problem was identified: he did not have a scheduling date for payments to suppliers. Complementarily, problems were detected in: the support of expenses for per diem of each driver, there was no supporting documentation of petty cash expenses, there was duality of functions, and loss of time in the area of accounting assistant. To solve this problem, the following solution actions were taken: payment policies were established by type of payment, and by suppliers, payment dates and the procedure flowchart of payments to suppliers was put into effect. It was applied, the functions manual of accounting assistant, the flowchart of sustentation of expenses for travel expenses of the drivers, the information was modernized with instructive letters, web portal and mails to the suppliers, finally, the business accounting plan was applied for the best assignment of accounts, for timely information in management decision making. All these actions allowed me to arrive at the main conclusion: Payments policies were established to suppliers, managing to identify the types of payments and suppliers, reaching a better relationship and negotiation in terms and means of payment.